Production of Biodiesel From LGCPO (Low-Grade Crude Palm Oil) Through In-Site Transesterification With The Addition of Catalysts: Produksi Biodiesel dari LGCPO (Low Grade Crude Palm Oil) Melalui Transesterifikasi In-Situ dengan Penambahan Katalis Basa - Rismul Trianto Salawali; Mustika Ibrahim; Mega Fia Lestari (Unit Penelitian dan Pengabdian Kepada Masyarakat, AK-Manufaktur Bantaeng, 2023)
Biodiesel is one of the alternative fuels to replace diesel fuel derived from petroleum. The purpose of this study is to determine the use of LGCPO (low-grade crude palm oil) as biodiesel. Biodiesel preparation is carried out by esterification of 7% H2SO4 catalyst and methanol 1:30 (w/w) at 60 oC for 2 hours. Transesterification was carried out at 60 oC for 1 hour with 1.5% KOH catalyst (w/w) and 35% methanol (w/w). Before synthesizing, the water content obtained was 0.40% and the ALB was 7.46%. Furthermore, specification testing was carried out on biodiesel based on the Indonesian National Standard (SNI) 7182-2015 that has been set, which shows an acid number of 0.4 mg NaOH/gg, density of 860.4 kg/mm3 (simplo) and 866.1 kg/m3 (duplo), and a kinematic viscosity of 2.93 mm2/s at 40 oC.Characterization was carried out by FTIR spectrophotometer analysis, which showed the presence of ester functional groups that are characteristic of synthesized biodiesel: the presence of C-O groups from esters at wavenumbers 1244.13 cm1 and 1170.83 cm1, and the presence of C=O groups from esters at wavenumbers 1743.71 cm1. In addition, Gas Chromatography-Mass Spectroscopy (GC-MS) analysis was also carried out, which showed the presence of six methyl ester (biodiesel) compounds, namely methyl myristate, methyl palmitate, methyl stearate, methyl oleate, methyl linoleate, and methyl arachidate.